Multiple Sensor Scheduling in a Dual-Hop Underwater-Acoustic/Terrestrial-RF System - Romya Bhatnagar
In this paper, we consider a dual-hop heterogeneous underwater acoustic/terrestrial radio frequency system. To accommodate multiple underwater sensors, we employ two multi-sensor scheduling techniques: generalised order sensor scheduling and round-robin scheduling. The underwater acoustic network is connected to the terrestrial radio frequency link through a decode and forward relay, serving as an acoustic-radio frequency communication node. This node is associated with the floating vehicle which is present on the water surface. Each underwater acoustic channel is considered to have Rayleigh fading with outdated channel state information. For the radio frequency link, we adopt Nakagami-m fading. For the presented dual-hop system, the closed-form analytical expressions of outage probability, average bit error rate, and effective capacity are derived. For better understanding, the asymptotic results for outage probability and average bit error rate are also derived. The diversity order and coding gain are also yielded for both the scheduling methods. Also, the analytical result is verified by Monte-Carlo simulations. Furthermore, the average fairness is evaluated for underwater multi-sensor networks.